High-intensity interval training ameliorates endothelial dysfunction through adropin, nitric oxide, MR-proADM, and copeptin changes in overweight subjects - Abbasian, Sadegh; Ravasi, Ali Asghar; Soori, Rahman; Aydin, Suna; Choobineh, Sirous; Aydin, Suleyman (Springer Int Publ Ag, 2022)
Purpose The purpose of this study was to determine adropin, NO, MR-proADM, and copeptin changes following four different types of high-intensity interval training (HIIT) in men with overweight. Methods In the current study, 45 overweight participants were included in the pre-intervention assessments and randomly assigned to the following groups: (1) control, (2) HIIT bike, (3) HIIT short-treadmill, and (4) HIIT long-treadmill groups. The participants were given 10-min sessions of HIIT intervention between 85 and 95% of VO2peak, followed by 1-min inactive recovery at three sessions/week for 8 weeks. Body composition, VO2peak, ultrasound imaging, diabesity-related risk factors, adropin, NO, MR-proADM, and copeptin were also assessed before and following the HIIT interventions. Results There was a statistically significant elevation in adropin and NO levels (p < 0.05), while MR-proADM and copeptin were notably more decreased than those of the control group following the 8 weeks of HIIT interventions (p < 0.01). However, no statistically significant decrease was observed in carotid/femoral intima-media thickness (c/f-IMT) values following the 8-week HIIT interventions, while statistically significant reductions were demonstrated in participants who had no atherosclerotic plaque or IMT < 0.9 mm (p < 0.05). Conclusions In conclusion, HIIT had a greater effect on IMT remodeling of the femoral artery than of the carotid artery. Decreased MR-proADM and copeptin and increased adropin levels might act as a physiological surrogate of endothelial dysfunction through increased NO-related signaling pathways in participants with overweight following high-intensity interval training.
Keywords: Adropin; Exercise training; Intima-media thickness; Vascular functional surrogates